2014
DOI: 10.1039/c3cc47830k
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that steric factors modulate reactivity of tautomeric iron–oxo species in stereospecific alkane C–H hydroxylation

Abstract: A new iron complex mediates stereospecific hydroxylation of alkyl C-H bonds with hydrogen peroxide, exhibiting excellent efficiency. Isotope labelling studies provide evidence that the relative reactivity of tautomerically related oxo-iron species responsible for the C-H hydroxylation reaction is dominated by steric factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
2
33
0
1
Order By: Relevance
“…A particularly useful diiron(II) complex for comparison is [Fe II 2 ( μ -OH)( μ -OH 2 )(TPA) 2 ] 3+ (TPA = tris(2-pyridylmethyl)amine) [74], which was found to have respective Fe II - μ -OH and Fe II - μ -OH 2 bonds averaging 2.07 and 2.17 Å, values that support our proposed assignment of the 2.07-Å scatterer in hDOHH- R as a hydroxo bridge. The remaining two scatterers at 2.18 Å have Fe–O distances consistent with either terminal (2.04 – 2.16 Å, Table S8) [51, 77, 7983] or bridging water ligands (2.13 – 2.40 Å) [77, 78], but the Fe•••Fe distance of 3.22 Å observed for [Fe II 2 ( μ -OH)( μ -OH 2 )(TPA) 2 ] 3+ is too short to match the distance deduced for hDOHH- R .…”
Section: Discussionmentioning
confidence: 99%
“…A particularly useful diiron(II) complex for comparison is [Fe II 2 ( μ -OH)( μ -OH 2 )(TPA) 2 ] 3+ (TPA = tris(2-pyridylmethyl)amine) [74], which was found to have respective Fe II - μ -OH and Fe II - μ -OH 2 bonds averaging 2.07 and 2.17 Å, values that support our proposed assignment of the 2.07-Å scatterer in hDOHH- R as a hydroxo bridge. The remaining two scatterers at 2.18 Å have Fe–O distances consistent with either terminal (2.04 – 2.16 Å, Table S8) [51, 77, 7983] or bridging water ligands (2.13 – 2.40 Å) [77, 78], but the Fe•••Fe distance of 3.22 Å observed for [Fe II 2 ( μ -OH)( μ -OH 2 )(TPA) 2 ] 3+ is too short to match the distance deduced for hDOHH- R .…”
Section: Discussionmentioning
confidence: 99%
“…Eine alternative Strategie zur Erhöhung der Reaktivität von Oxidoeisen(IV)‐Komplexen beruht auf dem Austausch der äquatorialen Pyridinliganden durch N ‐Methylbenzimidazolyl‐Substituenten. Der durch den sp 2 ‐Charakter und die Starrheit dieser Substituenten erzwungene sterische Anspruch im äquatorialen Bereich sollte größer sein als derjenige der α‐H‐Substituenten an den senkrechten Pyridindonoren . Andererseits können die relativen Donorfähigkeiten von Pyridinen und Benzimidazolen anhand der p K a ‐Werte ihrer konjugierten Säuren als sehr ähnlich eingeschätzt werden (5.22 für Pyridin und 5.41 für Benzimidazol).…”
Section: Reaktivität Von Oxidometallkomplexenunclassified
“…1). 18 We have previously observed that an (N-methyl)benzimidazolyl-containing ligand can enhance the catalytic reactivity of an Fe(II) complex in stereospecific C-H hydroxylation reactions, 27 and were therefore interested in investigating the influence of a chiral ligand containing (N-methyl)benzimidazolyl donor moieties on Fe(II)-catalyzed asymmetric epoxidation. For this purpose we have employed the tetradentate chiral ligand, Fig.…”
Section: Introductionmentioning
confidence: 99%